Pemberdayaan Kelompok Nelayan Pesisir Pantai Tamperan Pacitan Melalui Pengembangan Teknologi Informasi - Esti Rahayuningtyas, Tri; Umam, Choerul; Widyatmoko, Widyatmoko; Pramudyawardana Kusuma Negara, Wana; Pradipta Himawan, Mahadika; Ibnu Fitroh Sukono Putra, Febrianur; Rachmawansyah, M. Sandia; Rifqi Ardiansyah, M. Jihatur; Anjasari, Triska (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The lives of communities on the coast are mostly active in port areas with extraordinary natural resources and the potential to be empowered through programs to improve the quality of life of fishing communities on the coast. Of the many ports for empowering fishing communities is the Tamperan Pacitan coastal fishing port. The area used for fishermen's activities has an infrastructure capable of anchoring small, medium-sized, and large-scale fishing boats. Pacitan's Tamperan Port, although at a traditional level, can maximize its existing potential and will have a significant impact on fishermen to improve their economic standard of living. One of the problems faced by fishermen groups on Pacitan's Tamperan coast is the lack of promotion or information about the fishermen's catches in the form of fish species that are known to the wider community. It is hoped that this service will increase knowledge for fishermen groups so that their activities and activities are known to the public through the development of information technology in the form of websites. This community service activity includes website application development activities for fishermen and ship owners. It is hoped that in the future this website will be able to provide changes to the economic growth of the fishermen themselves. However, attention needs to be paid to the field of human resources so that it can keep pace with technological developments that are necessary and beneficial for fishermen. In this way, port management and fishermen can run optimally. Support from various parties must of course be supported, including from the local government, to create a port that has great benefits based on information technology.